Effect of Diffusion on Dissimilar Welded Joint between Al0.8CoCrFeNi High-Entropy Alloy and S235JR Structural Steel - Ionelia Voiculescu; Victor Geanta; Elena Violeta Stefanescu; George Simion; Elena Scutelnicu (Metals, 2022)
This research focused on the investigation of the metallurgical behavior of the Al0.8CoCrFeNi high-entropy alloy and S235JR structural steel, welded with (Ni, Fe)-rich filler metal, by the Gas Tungsten Arc Welding (GTAW) method. The electric arc and the welding pool were protected against the contamination with gases from the environment, by employing high-purity Ar 4.8 inert gas that plays an important role in reducing the oxidation effects and the development of cracks in the weld and the adjacent areas. The microstructure and microhardness analysis did not reveal the existence of fragile phases, cracks, inadequate penetration, or other imperfections, showing an appropriate adhesion between the deposited metal and the substrates. At the interface between the Ni-rich weld metal and the high-entropy alloy, a higher hardness (448 HV0.2) than in the base material (358 HV0.2) was measured. Energy-dispersive X-ray analysis (EDS), performed at the interface between the weld metal and the base materials, did not show significant modifications of Co, Fe, and Cr percentages. However, during the investigation, significant variations in Al and Ni concentrations were observed, caused by the fast diffusion of chemical elements, and the development of hard (Ni, Al)-rich compounds. In some areas of the deposited metal, located at a distance of about 10 µm from the interface, the percentages of Ni and Al were higher than in the high-entropy alloy base material, being around 41% by weight Ni and over 13% by weight Al, while the concentrations of the Co, Cr, and Fe elements proportionally decreased (i.e., approximately 14% by weight Co, 12% by weight Cr, and 17% by weight Fe). The development of Ni3Al and NiAl compounds was also noticed, whose formation was determined by the local chemical concentration and the temperature reached in the vicinity of the diffusion zone. The XRD analysis showed a group of X-ray peaks in the Al0.8CrFeCoNi alloy that corresponded to both α-type—BCC and FCC phases. The crystallite size of the high-entropy alloy investigated was found to be 22.05 nm. Despite the diffusion phenomenon, if filler materials and process parameters are appropriately selected, quality joints of high-entropy alloys and structural steels can be carried out under good welding conditions.